Fipronil impairs the GABAergic brain responses of Nile Tilapia during the transition from normoxia to acute hypoxia - Dourado, Priscila L. R. [UNESP]; Lima, Daína; Mattos, Jacó J.; Bainy, Afonso C. D.; Grott, Suelen C.; Alves, Thiago C.; de Almeida, Eduardo Alves; da Silva, Danilo G. Humberto (Wiley, 2023)
γ-aminobutyric acid (GABA) is one of the main neurotransmitters involved in the adaptation processes against the damage that hypoxia can cause to the brain. Due to its antagonist action on GABA receptors, the insecticide fipronil can turn the fish more susceptible to the negative effects of hypoxia. This study aimed to understand better if fipronil affects these GABAergic responses of Tilapia ahead to hypoxia. Oreochromis Niloticus (Nile Tilapia) were exposed for 3 and 8 h to fipronil (0.0, 0.1, and 0.5 µg.L−1) under normoxia (dissolved O2 > 6 mg.L−1) and moderate hypoxia (dissolved O2 < 2 mg.L−1) conditions. Briefly, hypoxia caused opposite effects on the gene transcription of the evaluated ionotropic and metabotropic GABA receptors. Unexpectedly, we obtained reduced HIF1A mRNA and brain GABA levels, mostly in the first 3 h of the experiment, for the hypoxic group compared with the normoxia one. Besides that, we also demonstrated that the insecticide fipronil impairs the brain GABAergic signaling of a hypoxia-tolerant fish during the transition from a normoxic to an acute hypoxic state. Thus, these results predict the relevant impact on the brain metabolic adaptations of fishes exposed to such stressful conditions in an aquatic environment, as well as the effects of fipronil in the GABAergic responses to hypoxia, which in turn may have ecological and physiological significance to hypoxia-tolerant fishes exposed to this insecticide.
Keywords: Antioxidant enzymes; Fipronil; Fish; GABA receptors; HIF-1A